Nox philologiae : Aulus Gellius and the fantasy of the Roman library - Gunderson, Erik (Wisconsin studies in classics., 2009)
This esoteric and original study focuses on the equally singular work of Aulus Gellius--a Roman author and grammarian (ca. 120-180 A.D.), possibly of African origin. Gellius's only work, the twenty-volume "Noctes Atticae"," "is an exploding, sometimes seemingly random text-cum-diary in which Gellius jotted down everything of interest he heard in conversation or read in contemporary books